2017
DOI: 10.3171/2016.7.peds16282
|View full text |Cite
|
Sign up to set email alerts
|

Blunt prenatal trauma resulting in fetal epidural or subdural hematoma: case report and systematic review of the literature

Abstract: Blunt prenatal trauma is known to have consequences to the developing brain, and can result in subdural hematoma (SDH) or epidural hematoma (EDH). The authors present a case of blunt prenatal trauma resulting in a fetal SDH, intraparenchymal hematoma, and intraventricular hemorrhage, and perform a systematic review of the literature. This systematic review was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Relevant studies (up to April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…There are several etiological causes of intrauterine intracranial hemorrhage such as trauma, perinatal asphyxia, drug use affecting platelet activity, infection, and congenital factor deficiency. However, there is a closer relationship between intrauterine subdural hematomas and maternal trauma than other etiological causes [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several etiological causes of intrauterine intracranial hemorrhage such as trauma, perinatal asphyxia, drug use affecting platelet activity, infection, and congenital factor deficiency. However, there is a closer relationship between intrauterine subdural hematomas and maternal trauma than other etiological causes [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Joseph et al in 2017 with PubMed publications, a total of 14 cases have been reported to date. Only 4 of these cases were isolated subdural hematoma [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of fetal subdural or epidural hematoma after maternal trauma identified 14 cases, 9 of them secondary to motor vehicle accidents as with our patient. Of these 14 cases 3 patients experienced intrauterine fetal demise and 3 neonatal demise [ 6 ]. While true mortality and morbidity rates are unknown, the seemingly high risks for these outcomes speak to the importance of timely diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Прежде всего следует отметить экстренное кесарево сечение, выполненное в кратчайшие сроки на фоне непродолжительного безводного периода, отсутствия родовой деятельности и подозрения на отслойку плаценты и позволившее избежать длительного внутриутробного наблюдения за жизнедеятельностью плода, во время которого его состояние могло ухудшиться до критического [20,52]. Следующим важным моментом стала форма ЧМТ, так как, несмотря на в целом неблагоприятные исходы при внутримозговых кровоизлияниях (смертность достигает 43%) [41], показано, что субдуральные гематомы имеют менее тяжелое течение и лучшие исходы (до ⅔ выживших младенцев остаются неврологически сохранными), нежели тяжелые внутрижелудочковые кровоизлияния [40]. И наконец, родоразрешение пришлось на поздний срок беременности, когда органы и системы организма, в том числе головной мозг, в достаточной степени сформированы.…”
Section: обсуждение и заключениеunclassified
“…Тяжелые внутриутробные ЧМТ, в том числе переломы свода черепа с внутримозговыми кровоизлияниями, согласно данным многих авторов, могут сопровождаться 90-100% летальностью [11,[35][36][37]. Вместе с тем регулярно публикуются работы, свидетельствующие о неоднозначности подобной точки зрения и описывающие случаи благополучного родоразрешения [15] и даже нейрохирургического вмешательства [38] и выписки пациента из стационара как с клинически значимыми неврологическими нарушениями (до 55% случаев) [39], так и без заметного неврологического дефицита при последующем кратковременном наблюдении [40,41].…”
unclassified